Improving learning outcomes on wind direction material in social science subjects through the demonstration method among third-grade students at min 5 demak - Maria Nurul Qoyyimah (At Turots: Jurnal Pendidikan Islam, 2025)
Social Studies learning generally requires students to memorize lesson material, so the use of appropriate learning strategies needs to be developed and implemented as effectively as possible in order to achieve maximum goals. However, there are still teachers who teach in a monotonous manner. This causes students to become bored and tend to be passive in learning, resulting in low learning outcomes in Social Studies. The main problem that this study aims to address is: Can the application of the demonstration method improve the learning outcomes in Social Studies, specifically on the topic of cardinal directions, for third-grade students at MIN 5 Demak. This research uses classroom action research. The classroom action research was carried out in two cycles, namely Cycle I and Cycle II. Each cycle consists of four stages: planning, implementation, observation, and reflection. The data collection methods used include observation, tests, and documentation. The findings of this study indicate that the application of the demonstration method can improve the learning outcomes in Social Studies on the topic of cardinal directions for third-grade students at MI Negeri Mlaten, Mijen District, Demak Regency. This can be seen from the discussion of the average student learning scores, which increased from 46.42% in the pre-cycle to 64.28% in Cycle I, and further increased to 100% in Cycle II.Bottom of Form